The Role of Regional and International Actors in Combating Terrorism in West and East Africa: A Comparative Study of ECOWAS and AMISOM - Ihedioha, Yagazie E. Ihedioha; Badru, Ronald Badru (African Journal of Stability and Development (AJSD), 2025)
The rising threat of terrorism in Africa, particularly in West and East Africa, has prompted the increasing involvement of regional and international actors in counterterrorism efforts. This study critically examines and compares the roles of the Economic Community of West African States (ECOWAS) and the African Union Mission in Somalia (AMISOM) in combating terrorism in their respective regions. Despite the existence of several state-level and multinational initiatives, terrorist groups such as Boko Haram and Al-Shabaab continue to exploit weak governance, political instability, and socio-economic grievances. The study addresses the problem of limited comparative analyses of regional counterterrorism responses in Africa and evaluates the extent to which regional organisations have influenced security outcomes. The objectives of the study are to analyse the strategies employed by ECOWAS and AMISOM, assess the effectiveness of regional cooperation in counterterrorism, and identify challenges and lessons learned. Guiding research questions include: What are the main counterterrorism approaches of ECOWAS and AMISOM? How effective are these approaches in addressing terrorism? What are the shared challenges, and what lessons can be drawn for future regional interventions? Methodologically, the study adopts a qualitative, comparative case study approach, drawing on document analysis, existing literature, and institutional reports. Findings reveal that AMISOM has been more militarily robust, with notable territorial gains, while ECOWAS has prioritised diplomacy and legal frameworks. Both institutions, however, face structural constraints, funding challenges, limited operational capacity, and over-reliance on international partners. The study concludes that while regional organisations play a critical role in Africa’s security landscape, sustainable counterterrorism requires a balance between military force and political, economic, and social interventions. It recommends strengthening institutional capacity, improving coordination, promoting local ownership, and integrating human rights protections into all regional security frameworks.